Combining Congenital Heart Surgical and Interventional Cardiology Outcome Data in a Single Database: The Development of a Patient-Centered Collaboration of the European Congenital Heart Surgeons Association (ECHSA) and the Association for European Paediatric and Congenital Cardiology (AEPC) - Jacobs, Jeffrey P.; Krasemann, Thomas; Herbst, Claudia; Tobota, Zdzislaw; Maruszewski, Bohdan; Fragata, Jose; Ebels, Tjark; Vida, Vladimiro L.; Mattila, Ilkka; Kansy, Andrzej; Asfour, Boulos; Hörer, Jürgen; et al. (World Journal for Pediatric and Congenital Heart Surgery, 2023)
The European Congenital Heart Surgeons Association (ECHSA) Congenital Database (CD) is the second largest clinical pediatric and congenital cardiac surgical database in the world and the largest in Europe, where various smaller national or regional databases exist. Despite the dramatic increase in interventional cardiology procedures over recent years, only scattered national or regional databases of such procedures exist in Europe. Most importantly, no congenital cardiac database exists in the world that seamlessly combines both surgical and interventional cardiology data on an international level; therefore, the outcomes of surgical and interventional procedures performed on the same or similar patients cannot easily be tracked, assessed, and analyzed. In order to fill this important gap in our capability to gather and analyze information on our common patients, ECHSA and The Association for European Paediatric and Congenital Cardiology (AEPC) have embarked on a collaborative effort to expand the ECHSA-CD with a new module designed to capture data about interventional cardiology procedures. The purpose of this manuscript is to describe the concept, the structure, and the function of the new AEPC Interventional Cardiology Part of the ECHSA-CD, as well as the potentially valuable synergies provided by the shared interventional and surgical analyses of outcomes of patients. The new AEPC Interventional Cardiology Part of the ECHSA-CD will allow centers to have access to robust surgical and transcatheter outcome data from their own center, as well as robust national and international aggregate outcome data for benchmarking. Each contributing center or department will have access to their own data, as well as aggregate data from the AEPC Interventional Cardiology Part of the ECHSA-CD. The new AEPC Interventional Cardiology Part of the ECHSA-CD will allow cardiology centers to have access to aggregate cardiology data, just as surgical centers already have access to aggregate surgical data. Comparison of surgical and catheter interventional outcomes could potentially strengthen decision processes. A study of the wealth of information collected in the database could potentially also contribute toward improved early and late survival, as well as enhanced quality of life of patients with pediatric and/or congenital heart disease treated with surgery and interventional cardiac catheterization across Europe and the world.
CRIS-Team Scopus Importer:2023-07-21
Keywords: cardiac surgery; congenital heart disease; database; interventional cardiology; nomenclature; pediatric; pediatric heart disease